2015
DOI: 10.1055/s-0035-1546827
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Testing in the Era of Direct or Non–Vitamin K Antagonist Oral Anticoagulants: A Practical Guide to Measuring Their Activity and Avoiding Diagnostic Errors

Abstract: A new generation of antithrombotic agents has recently emerged. These provide direct inhibition of either thrombin (factor IIa [FIIa]) or FXa, and are increasingly replacing the classical anticoagulants (heparin and coumarins such as warfarin) in clinical practice for a variety of conditions. These agents have been designated several acronyms, including NOACs, DOACs, and TSOACs, respectively, referring to ew (ovel; on?vitamin K antagonist) ral ntioagulant, irect ral ntioagulant, and arget-pecific ral ntioagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 137 publications
0
26
0
Order By: Relevance
“…15 In contrast, the role of the tests in guiding dosing in the ambulatory setting remains controversial, partly because of questions about the choice of test and target range.…”
Section: Coagulation Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In contrast, the role of the tests in guiding dosing in the ambulatory setting remains controversial, partly because of questions about the choice of test and target range.…”
Section: Coagulation Testsmentioning
confidence: 99%
“…15 However, as the relationships between each of these tests and anticoagulant concentrations varies by drug and by laboratory, interpretation should be performed in consultation with local specialists. Specific advice about interpretation of coagulation tests is available from the Australasian Society of Thrombosis and Haemostasis.…”
Section: Coagulation Testsmentioning
confidence: 99%
“…A large number of studies have consistently demonstrated the accuracy and sensitivity of drug-specific anti-factor Xa chromogenic assays for the quantitative measurement of rivaroxaban, as summarized in a comprehensive literature review. 31 These assays (calibrated with rivaroxaban) can measure a wide range of rivaroxaban plasma concentrations that cover the expected levels after therapeutic doses ( Figure 1 ) and are, therefore, recommended by the EHRA and the rivaroxaban – Summary of Product Characteristics. 1 , 5 However, the longer turnaround time to obtain the test results makes them less convenient than PT in emergency situations.…”
Section: Laboratory Testing Of Doacsmentioning
confidence: 99%
“…Moreover, monitoring dabigatran plasma concentrations has the potential to improve safety and efficacy profiles as compared to fixed dosage [ 58 , 59 ]. Therapeutic drug monitoring of DOACs is supported by population studies which demonstrated a wide range of plasma dabigatran concentrations in different patient groups and at different time points although drug concentrations remained within the putative therapeutic range [ 60 ]. Variations in plasma concentration are ascribed to drug interactions, differences in absorption in the gastrointestinal tract, and clearance by the liver and kidneys [ 61 ].…”
Section: Advantages and Disadvantages Of Vka And Doacsmentioning
confidence: 99%